Frequency Of Colonic Lesions In Acromegaly (Journal of Pharmaceutical Negative Results, 2023)
Background and Aim: Acromegaly is an uncommon condition that affects 4-6 people per million each year. Acromegaly increases mortality and morbidity caused by cardiovascular and pulmonary complications, as well as cancers originating mostly in the colon. The purpose of the current study was to determine the frequency of colonic lesions in acromegaly.Patients and Methods: This retrospective cohort study was carried out on 63 patients diagnosed as Acromegaly visiting Endocrine Clinic in JPMC from 1st April 2007 till 31st March 2023. Detailed history, clinical examination and colonoscopic findings were recorded in a predesigned structured proforma. Clinical and hormonal profiles and colonoscopic findings were assessed in this time period.Results: The overall mean age was 32.10±12.39 years. Patients were distributed into three groups based on their age as follows: 27 (42.9%) in 10-30 years, 23 (36.5%) in 31-50 years, and 13 (20.6%) >51 years. There were 30 (47.6%) male and 33 (52.4%) females. About 37 (58.7%) patients had complaint of headache. On diagnosis, the incidence of acromegaly, postop and radio acromegaly, postop acromegaly, and post radio acromegaly was 35 (55.6%), 2 (3.2%), 7 (11.1%), and 1 (1.6%) respectively. Among 63 acromegaly patients, the incidence of adenomatous, inflammatory, hyperplastic, hamartomatous polyps, benign epithelial polyps, cap polyps, lipomatous polyps, angiomatous polyps, and lymphoid were 29 (46%), 9 (14.3%), 9 (14.3%), 4 (6.3%), 4 (6.3%), 3 (4.8%), 2 (3.2%), 1 (1.6%), and 2 (3.2%) respectively.Conclusion: The present study found that Acromegaly has a small association with colonic lesions. Most patients do not have any bowel symptoms and have normal colon on colonoscopies.